Identification And Characterization Of Fusarium Species From Highlands In Malaysia - Manshor, Nurhazrati (2014)
Fusarium is one of the heterogeneous genera of saprophytic, pathogenic, and toxigenic fungi distributed worldwide. However, such an important genus is considered to be one of the most highly diversified, thus difficult to identify and classify. Recently, several Fusarium species normally found in the temperate and subtropical regions were also reported to be in the highlands of tropical areas, including Malaysia. This research was to identify Fusarium species in context of occurrence, diversity, and toxigenicity. Phase sampling was done randomly from variable hosts and substrate in three locations, Cameron Highlands, Fraser’s Hill and Kinabalu Park. The samples were plated on a semi-selective medium (pentachloronitrobenzene agar) and incubated in a standard incubation conditions (27+1°C). One-hundred twenty three (123) Fusarium isolates were single-spored and identified based on the morphological characteristics. Four species were identified i.e. F. graminearum (86.2%), followed by F. venenatum (12.2%), F. avenaceum (0.8%) and F. sporotrichioides (0.8%). Molecular characterization and mycotoxin profiles were used to support the morphological data. The molecular characterization were carried out by using PCR-RFLP of the rDNA intergenic spacer (IGS) region and DNA sequences using Translation α-Elongation Factor (TEF) gene. BLAST search for sequence similarity by using GenBank database which demonstrated 88% - 99% whereas for Fusarium Database was between 89% - 99%.